If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 2) = 39 Reorder the terms: 3(2 + 5x) = 39 (2 * 3 + 5x * 3) = 39 (6 + 15x) = 39 Solving 6 + 15x = 39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 15x = 39 + -6 Combine like terms: 6 + -6 = 0 0 + 15x = 39 + -6 15x = 39 + -6 Combine like terms: 39 + -6 = 33 15x = 33 Divide each side by '15'. x = 2.2 Simplifying x = 2.2
| x/13+12=19 | | f(x)=x^2-10x+1 | | 2a(5a-13)=47 | | H=16x^2+112t+960 | | 5-5.2x=1-2.8x | | 3x+6(0)=12 | | 2p+2+p=-29 | | 3(x-3)+2=5 | | 10-y=-24-4x | | 19w-20w+-20=-9 | | x/12-5=6 | | 8(t+2)-3(2-4)=6(t-7)+8 | | 3r^6-11r^5-20r^4=0 | | 3x-2+12=x+10 | | 0.50x+0.25(50)=21.5 | | 3(0)+6y=12 | | x-36=3(28-x) | | x(40.00+15.25+9.50)=213.25 | | -4(b-6)=-7(b+6)+3b | | X^2-2-14=0 | | 7x+5=6-(6x-6) | | 3-4x+6x=-21 | | 16x^2-24m+9=0 | | Y=-2.5x^2+10x+8 | | 8-7x-6x=8 | | 6-xw=vw+1 | | X-(1+3(3))2=17 | | 2x^5+x^4-2x-1=0 | | (x)(y)=20 | | y=0.04x | | 0=-2.5x^2+10x+8 | | 21-3t=4t |